Brain Regional Differences in Hexanucleotide Repeat Length in X-Linked Dystonia-Parkinsonism Using Nanopore Sequencing. (August 2021) - Reyes, Charles Jourdan; Laabs, Björn-Hergen; Schaake, Susen; Lüth, Theresa; Ardicoglu, Raphaela; Rakovic, Aleksandar; Grütz, Karen; Alvarez-Fischer, Daniel; Jamora, Roland Dominic; Rosales, Raymond L.; Weyers, Imke; König, Inke R.; et al.
Abstract : Objective: Our study investigated the presence of regional differences in hexanucleotide repeat number in postmortem brain tissues of 2 patients with X-linked dystonia-parkinsonism (XDP), a combined dystonia-parkinsonism syndrome modified by a (CCCTCT)n repeat within the causal SINE-VNTR- Alu retrotransposon insertion in the TAF1 gene. Methods: Genomic DNA was extracted from blood and postmortem brain samples, including the basal ganglia and cortex from both patients and from the cerebellum, midbrain, and pituitary gland from 1 patient. Repeat sizing was performed using fragment analysis, small-pool PCR-based Southern blotting, and Oxford nanopore sequencing. Results: The basal ganglia ( p < 0.001) and cerebellum ( p < 0.001) showed higher median repeat numbers and higher degrees of repeat instability compared with blood. Conclusions: Somatic repeat instability may predominate in brain regions selectively affected in XDP, thereby hinting at its potential role in disease manifestation and modification.